Understanding The Character of Pancasila Students in The Perspective of Maqasid Sharia - Islamy, Athoillah; Ubaidillah; Zulihi; Siswanto, Eko (Ijtimā iyya Journal of Muslim Society Research, 2024)
The purpose of this qualitative study with a normative-philosophical approach and content analysis is to identify the dimensions of maqasid sharia values in the Pancasila Student Profile. The construction of maqasid sharia concept development formulated by Jasser Auda became the basis of perspective. Data were collected through documentation techniques, and data were analysed using reduction, presentation, and verification. This study concludes that various pillars in the Pancasila Student Profile contain maqasid sharia values, including the dimension of hifz tadayun value in the pillar of strengthening the character of religious students. Furthermore, the value of hifz ummah in strengthening the character of humanist and pluralist students. Then, the value of hifz fikr in strengthening the character of independent, critical and creative students. This study confirms the synergy of fiqh values with education (tarbiyah) in strengthening the character of Pancasila for Indonesian students